(untitled) (Indian Journal of Public Health Research & Development, 2022)
Background: Cardiovascular diseases, especially coronary heart disease (CHD), are epidemic in India. The Registrar General of India reported that CHD led to 17% of total deaths and 26% of adult deaths in 2001-2003, which increased to 23% of total and 32% of adult deaths in 2010-2013. In India, studies have reported increasing CHD prevalence over the last 60 years, from 1% to 9%-10% in urban populations and <1% to 4%-6% in rural populations. Important risk factors for CHD in India are dyslipidemias, smoking, diabetes, hypertension, abdominal obesity, psychosocial stress, unhealthy diet, and physical inactivity. Suitable preventive strategies are required to combat this epidemic. Aim: The aim of the study is to assess and stratify the risk of coronary artery disease among adults. Materials and Methods: The research design used for this study is true experimental pre test post test control group design with follow up. Non probability Quota sampling technique will be used for this study. Sensitization programme is an intervention in which repeated administration of interventions to the participants to understand and involve in risk reduction strategies of coronary artery disease. Result: Frequency and Percentage distribution of study participants according to their risk of CAD. Majority 144(72.0%) of the study participants had low risk of CAD followed by 52(26.0%) of the study participants who had intermediate risk and remaining 4(2.0%) of the study participants had high risk. A total of 200 adults were completed the questionnaire. The sociodemographic data represented that frequency and percentage distribution of adults according to socio- demographic profile such as age, gender, religion, marital status, educational status, occupation, dietary habits, family history of heart disease, smoking habits and alcohol consumption. The BMI level of the adults depicts that majority 131(91.0%) had normal BMI, 6(4.2%) were overweight and 7(4.9%) under weight. Off high risk study subjects, majority 28(50.0%) had over weight and 14(25.0%) each of the study subjects had normal weight and obese respectively. In relation to adult stress majority 52(92.9%) were at moderate risk of illness and only 4(7.1%) were at risk illness. It was clear that coronary artery risk score were same between experimental and control group during pretest but the difference in risk scores was highly significant when compared with posttest-I, posttest-II and posttest-III. Hence the sensitization programme was effective on reduction of coronary artery disease among the adults and hence second hypothesis was proved. It was seen that there was no association between knowledge risk scores of coronary artery disease with their selected socio-demographic variables such as Age, Gender, Religion, Education, laborer, dietary habit, family History, smoking habits, alcohol consumption but it was highly associated with Marital Status. Conclusion: The study concludes that risk factor of coronary artery disease was highly associated with selected risk factors such as dietary habits, junk food consumption, family history, smoking habits, consumptions of alcohol, adult stress, BMI and physical activity.